The Santillana Codes : the civil codes of Tunisia, Morocco, and Mauritania - Stigall, Dan E. (Lexington Books, 2017)
"This book examines the Santillana Codes, legal instruments which form a distinct class of uniquely African civil codes and which are still in force today in a legal arc that extends from the Maghreb to the Sahel. [The author] presents the history of Santillana's seminal legislative effort and provides a comparative analysis of the substance of those codes, illuminating commonalities between Islamic law and European legal systems."--